Penguatan Pendidikan Karakter Religius Anak melalui Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Nurul Hikmah Desa Sahang - Devina Candra Kartika; Rifqi Humaida (Social Science Academic, 2025)
Instilling Islamic religious values from an early age is an important foundation for developing a child's religious and noble character. Madrasah Diniyah, as a non-formal religious educational institution, plays a strategic role in the internalization of these values. This study aims to describe the role of Madrasah Diniyah in shaping the Islamic character of children in Sahang Village and identify supporting and inhibiting factors in its implementation. A qualitative approach was used, using data collection techniques such as observation, in-depth interviews, and documentation. The results show that Madrasah Diniyah Takmiliyah Awwaliyah Nurul Hikmah in Sahang Village actively fosters Islamic values through activities such as worship, Quranic learning, morals, and teacher role models. The main supporting factors include a religious environment, parental involvement, and emotional closeness between teachers and students. Meanwhile, obstacles faced include limited infrastructure, low innovation in learning methods, and challenges from external influences from a less supportive social environment. This study recommends strengthening collaboration between madrasahs, parents, and the community to create a sustainable and holistic religious education ecosystem.